Long-term outcome of 56 patients after transnasal endoscopic repair of congenital choanal atresia - Yılmaz Topçuoğlu, Miray-Su; Plinkert, Peter K.; Federspil, Philippe A.; Baumann, Ingo (Acta oto-laryngologica, 2025)
Choanal atresia (CA) is rare. Unilateral CA (UCA) can be detected late in life. Recurrences following CA repair are challenging. To examine the long-term surgical and subjective outcomes in patients with CA and the reason for recurrences. Outcome of transnasal endoscopic repair of congenital CA was examined between 2010 and 2022 in 25 patients with UCA and 31 patients with bilateral CA (BCA). Demographics, surgical data, and postoperative course were investigated. Subjective outcomes with regard to function and quality of life were examined via a visual analogue scale (VAS). Twelve surgeries were performed in ten patients with BCA due to recurrence. Insufficiently resected posterior vomer, and granulation tissue growth caused recurrences. VAS demonstrated a significant improvement in function (p < 0.0001) and quality of life (p < 0.0001) following surgery in patients with UCA and BCA with the highest levels of postoperative satisfaction (median satisfaction score of 10). Insufficient vomer resections and granulation tissue cause recurrences. Patients with UCA exhibited substantial impairment in both function and quality of life. BCA requires immediate treatment at birth. But also, the treatment of patients with UCA should be timely, contingent on present symptoms, as CA repair significantly increase their quality of life.
Gesehen am 16.02.2026